UPAYA PENINGKATAN WELL-BEING PADA MASYARAKAT BERESIKO MELALUI STRATEGI PEMBENTUKAN STRENGTH-BASED COMMUNITY RESPONSE DI NAGARI KAMPUNG BARU, KABUPATEN PESISIR SELATAN - Satria Efandi; Riva Nadia Putri; Rifdha Wahyuni; Abdur Rahman; Ruqaya Annisa; Nurul Haq; Adewirli Putra; Wiya Elsa Fitri (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
The implementation of the Strength-Based Community Response program was primarily aimed at investigating the effectiveness of this approach in enhancing psychological functioning and well-being within a high-risk environment located in Nagari Kampung Baru, Pesisir Selatan Regency. This high-risk environment encompasses communities facing a multitude of complex challenges in the social, economic, and psychological realms. The intervention was carried out through a structured series of stages, commencing with the establishment of rapport with the respective community, followed by core activities, and concluding with program evaluation to measure its success and necessary follow-up actions. The entire population of Nagari Kampung Baru, Pesisir Selatan Regency, participated in this program with the broader goal of establishing a healthy and prosperous model village. The results derived from this program unequivocally demonstrate the effectiveness of the Strength-Based Community Response approach in improving individual psychological functioning while simultaneously stimulating the development of underutilized community resources. Participants engaged in these activities experienced a significant increase in their subjective well-being levels. Furthermore, they reported substantial improvements in self-awareness, social relationships, and their perception of their ability to control their personal lives. In conclusion, the practical implications arising from this research effort include two main points: first, it reaffirms the potential application of similar approaches as effective intervention models to enhance the quality of life and well-being of individuals within their respective environments. Second, this approach underscores the importance of community engagement and empowerment in the pursuit of holistic well-being.